2016
DOI: 10.2500/ajra.2016.30.4278
|View full text |Cite
|
Sign up to set email alerts
|

Dead or Alive: Deoxyribonuclease I Sensitive Bacteria and Implications for the Sinus Microbiome

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In the sinonasal environment the rapid turnover of mucus covering respiratory epithelium from mucociliary clearance means that while the DNA persistence following cell death in the paranasal sinuses is not yet established, it may be less than estimates from other environments. In a study comparing live and dead bacteria using a novel deoxyribonuclease I (DNase I) dependent technique, it was found that up to 50% of the DNA identified in sinonasal samples may be derived from dead or damaged bacterial cells . In future studies assessing the impact of medical therapies on microbial profiles, both total and live bacteria‐derived DNA should be evaluated to avoid overestimating the living components of bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…In the sinonasal environment the rapid turnover of mucus covering respiratory epithelium from mucociliary clearance means that while the DNA persistence following cell death in the paranasal sinuses is not yet established, it may be less than estimates from other environments. In a study comparing live and dead bacteria using a novel deoxyribonuclease I (DNase I) dependent technique, it was found that up to 50% of the DNA identified in sinonasal samples may be derived from dead or damaged bacterial cells . In future studies assessing the impact of medical therapies on microbial profiles, both total and live bacteria‐derived DNA should be evaluated to avoid overestimating the living components of bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…All microbes in a habitat, their genes and metabolites Microbiota Collection of micro-organisms in a defined microenvironment Microbiota characterization is often based on conserved genes found on bacteria and fungi 20,21 Furthermore, part of the sequenced microbes might be transient in the human and animal body, 22 and phylogenetic differences can be seen depending on the use of different methods, and depending on the selected microbial genomic regions that are amplified in these studies. 23,24 These new microbiome concepts have opened avenues to explore the human and animal second genome, its functions and its importance in maintaining health, and how imbalances in these communities are associated with and possibly result in development of disease in the host.…”
Section: Microbiomementioning
confidence: 99%
“…Certainly, microbiome studies have some pitfalls as they account primarily for the presence of fragments from microbial genes, without considering whether these organisms are alive or dead, but they do allow us to categorize the history of the micro‐organisms inhabiting these different body surfaces . It is estimated that the great majority of microbes identified with next generation sequencing (NGS) studies (Box 2) are likely to be inactive or dead . Furthermore, part of the sequenced microbes might be transient in the human and animal body, and phylogenetic differences can be seen depending on the use of different methods, and depending on the selected microbial genomic regions that are amplified in these studies …”
Section: Introductionmentioning
confidence: 99%
“…Profiling the 16S (and ITS) variable regions enables researchers to catalog the taxonomic composition of the bacteria (or fungi) in the samples, up to a genus-level resolution. However, the information contained in these short sequences do not directly reveal if these bacteria (or fungi) are alive, or provide information about their metabolic states or their functions within living systems (55,56). Additionally, sequence read-counts do not directly correlate with the absolute bacterial load in the samples, in part, due to the variable copy numbers of the 16S gene in any given organism, dissimilarities of the universal 16S primers to the target genes of some of the microbes, and amplificationrelated artefacts introduced by the polymerase chain reaction (PCR), which is used to extract and amplify the 16S DNA fragments prior to sequencing (38).…”
Section: Measuring the Microbiome: Taxonomy And Functionmentioning
confidence: 99%